2013
DOI: 10.1007/s10126-013-9535-y
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of Hepatic Gene Expression in Juvenile Japanese Flounder Paralichthys olivaceus Fed Diets Supplemented with Fish or Vegetable Oils

Abstract: Gene expression profiling was performed in Japanese flounder Paralichthys olivaceus fed diets supplemented with fish oil (FO), linseed oil (LO), or olive oil (OO) for 6 weeks. The LO and OO groups showed significantly retarded growth, lower feed intake, lower protein efficiency ratio, and lower hepatosomatic index (P < 0.05). Liver fatty acid composition reflected the dietary fatty acid composition. Microarray analysis revealed that dietary n - 3 highly unsaturated fatty acid (HUFA) deficiency affected 169 tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 83 publications
5
8
0
Order By: Relevance
“…Up-regulation in srebp1 expression in liver was observed in fish fed the three VO in agreement with studies carried out in elovl5 −/− mice that indicated low levels of EPA and DHA lead to activation of this transcription factor [55]. Similar results have been obtained in other fish species when fed low levels of n-3 LC-PUFA or VO [50, 5658]. Up-regulation of srebp1 in VO-fed fish could lead to the regulation of srebp1 target genes such as fads2 , hl , lpl , cpt1a and cpt1b .…”
Section: Discussionsupporting
confidence: 88%
“…Up-regulation in srebp1 expression in liver was observed in fish fed the three VO in agreement with studies carried out in elovl5 −/− mice that indicated low levels of EPA and DHA lead to activation of this transcription factor [55]. Similar results have been obtained in other fish species when fed low levels of n-3 LC-PUFA or VO [50, 5658]. Up-regulation of srebp1 in VO-fed fish could lead to the regulation of srebp1 target genes such as fads2 , hl , lpl , cpt1a and cpt1b .…”
Section: Discussionsupporting
confidence: 88%
“…This result provided a new evidence for the involvement of SREBP-1 in the regulation of fish Fad by dietary fatty acids. Studies on Japanese flounder and Atlantic salmon also showed that fish fed diets supplemented with vegetable oils had higher gene expression levels of SREBP-1 compared with fish fed diets supplemented with fish oil (Morais et al, 2011;Limtipsuntorn et al, 2014). In mammal, it has been well known that SREBP-1 in particular SREBP-1c activity can be inhibited by PUFA such as α-linolenic acid (18:3n−3), γ-linolenic acid (18:3n−6), ARA (20:4n−6), EPA (20:5n−3), and DHA (22:6n−3) (Deng et al, 2002;Yoshikawa et al, 2002;Sekiya et al, 2003;Jump et al, 2005Jump et al, , 2008Espenshade, 2006;Leaver et al, 2008;Lecker et al, 2011;Lee and Song, 2012;Fukumitsu et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Dietary impacts on metabolism were determined by investigating the transcriptome of liver as the main organ integrating, processing and distributing dietary lipid 47 . Several studies analysing fish transcriptomic responses after substitution of dietary fish oil with vegetable oils have shown that, regardless of oil employed, metabolism and in particular lipid metabolism, are highly affected categories 47 48 49 50 51 For instance, genes involved in LC-PUFA biosynthesis were overrepresented among the DEG in liver of Atlantic salmon fed vegetable oils 47 . In the present study, this applies to fish fed both WCO and ECO diets, where these genes occupy the top positions among the 100 highest expressed genes in terms of intensity, when compared to fish fed FO.…”
Section: Discussionmentioning
confidence: 99%